4 - The Role of NGOs in Canada and the USA in the Transformation of the Socio-Cultural Structures in Africa: par Charles Quist-Adade - Van Wyk, Anita (Africa Development, 2007)
This paper aims to explain how International Non-Governmental Organisations (INGOs) in Canada and the United States of America assist in maintaining the West’s hegemonic position in ongoing globalisation process, with specific ref- erence to Africa. The process begins at the local community level with ordinary citizens in North America. These people are exposed to ‘development pornogra- phy’ through a plethora of visual, text and audio input via the mass media and popular culture, which present the African lifeworld as inferior and primitive, and African people as helpless, hapless, and in the throes of an unending series of epidemics on the short road to extinction. African cultures are portrayed as backward, atavistic, stuck in their primeval past, and needing ‘modernisation’ from the West. This African lifeworld is used to describe and portray Africa in ways that justify the importance of civil society organisations (CSOs) – chari- ties, aid workers, business people, missionaries and non-governmental organi- sations (NGOs) – in ‘intervening’ in the African continent’s seemingly inexora- ble human crises. INGOs, in turn, use this image as ‘compassion usury’, tugging on the heartstrings of North Americans to donate generously to various projects in Africa. Large amounts of money, goods and time are donated by ordinary people to help re-make the so-called inferior traditional lifeworlds of Africans in accordance with Western visions. In return, these donors receive generous rewards for their contributions, in the form of tax deductions, community recognition, and development fund awards. Many of these donors are so motivated that they become development tourists who regularly visit Africa, bringing back ‘mercy-soliciting’ images to raise funds and create jobs for NGOs. Horrific pic- tures further reinforce negative stereotypes and misconceptions about Africa. In this way CSOs, particularly those recognised in Canada and the USA as interna- tional NGOs, not only unwittingly export and impose North American values on Africans, but also serve and maintain the global status quo of Western hegemony and African dependence.